Life without lead : contamination, crisis, and hope in Uruguay - Renfrew, Daniel, 1974- (Critical environments. Nature, science, and politics, 2019)
Drawing on political ecology and science studies perspectives, 'Life without Lead' examines the social, political, and environmental dimensions of a devastating lead-poisoning epidemic.